Dominant negative umuD mutations decreasing RecA-mediated cleavage suggest roles for intact UmuD in modulation of SOS mutagenesis. - Battista, J R (1990)
The products of the SOS-regulated umuDC operon are required for most UV and chemical mutagenesis in Escherichia coli. The UmuD protein shares homology with a family of proteins that includes LexA and several bacteriophage repressors. UmuD is posttranslationally activated for its role in mutagenesis by a RecA-mediated proteolytic cleavage that yields UmuD'. A set of missense mutants of umuD was isolated and shown to encode mutant UmuD proteins that are deficient in RecA-mediated cleavage in vivo. Most of these mutations are dominant to umuD+ with respect to UV mutagenesis yet do not interfere with SOS induction. Although both UmuD and UmuD' form homodimers, we provide evidence that they preferentially form heterodimers. The relationship of UmuD to LexA, lambda repressor, and other members of the family of proteins is discussed and possible roles of intact UmuD in modulating SOS mutagenesis are discussed.